2013
DOI: 10.1111/cpf.12096
|View full text |Cite
|
Sign up to set email alerts
|

Normal values for heart rate variability parameters in children 6–8 years of age: the PANIC Study

Abstract: Same reference values for HRV parameters can be used in boys and girls. Although 5-min ECG recordings are preferable for measuring HRV, also 1-min recordings provide reliable data on most HRV parameters, especially those that mainly describe cardiac parasympathetic regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 31 publications
(53 reference statements)
2
40
1
4
Order By: Relevance
“…When comparing pre and post-surgical values between boys and girls, no significant differences were found in the same HRV parameters, which is consistent with previous studies that stated no differences in children HRV values according to gender [1,30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When comparing pre and post-surgical values between boys and girls, no significant differences were found in the same HRV parameters, which is consistent with previous studies that stated no differences in children HRV values according to gender [1,30].…”
Section: Discussionsupporting
confidence: 91%
“…Diminished HRV occurs when there's both autonomic inactivity and excessive sympathetic inputs [2], showing an ANS imbalance that may be induced by increased stress or autonomic neuropathy [30]. Time domain parameters (SDNN, RMSSD and pNN50) strongly reflect parasympathetic modulation of sinus node [4] and, although there´s not a consensus among the scientific community about frequency domain parameters, most authors consider HF component as an expression of vagal activity influenced by respiration and LF component as a reflection of both cardiac sympathetic and parasympathetic activity with predominance of the sympathetic discharge [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that previous investigations that evaluated the reliability of HRV in children (Winsley et al ., ; Leicht & Allen, ; Dietrich et al ., ; Seppala et al ., ), adults (Pitzalis et al ., ; Kobayashi, ; Pinna et al ., ; Nunan et al ., ) and patients with different diseases (Maestri et al ., ; Sacre et al ., ) have found lower ICC for HRV parameters than those observed in this study. Winsley et al .…”
Section: Discussionmentioning
confidence: 99%
“…obesity, high blood pressure, physical inactivity) (Urbina et al, 1998;Buchheit et al, 2007;Zhou et al, 2012;Farah et al, 2013Farah et al, , 2014Jaiswal et al, 2013). As a consequence, interest in analysing the HRV is growing, in order to provide a better understanding of these parameters as predictors of cardiovascular risk since youth (Srinivasan et al, 2002;Michels et al, 2013;Seppala et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies in adult patients have shown no difference in terms of HRV recovery between general and locoregional anesthesia. Likewise, Ireland et al did not find any difference on HRV indices after awakening according to the anesthetic agent used, while Seppälä et al showed that HRV did not vary between boys and girls . HRV could vary with pain levels.…”
Section: Discussionmentioning
confidence: 96%